Stress signaling in breast cancer cells induces matrix components that promote chemoresistant metastasis. Issue 10 (6th September 2018) - Insua‐Rodríguez, Jacob; Pein, Maren; Hongu, Tsunaki; Meier, Jasmin; Descot, Arnaud; Lowy, Camille M; De Braekeleer, Etienne; Sinn, Hans‐Peter; Spaich, Saskia; Sütterlin, Marc; Schneeweiss, Andreas; Oskarsson, Thordur
Abstract: Metastatic progression remains a major burden for cancer patients and is associated with eventual resistance to prevailing therapies such as chemotherapy. Here, we reveal how chemotherapy induces an extracellular matrix (ECM), wound healing, and stem cell network in cancer cells via the c‐Jun N‐terminal kinase (JNK) pathway, leading to reduced therapeutic efficacy. We find that elevated JNK activity in cancer cells is linked to poor clinical outcome in breast cancer patients and is critical for tumor initiation and metastasis in xenograft mouse models of breast cancer. We show that JNK signaling enhances expression of the ECM and stem cell niche components osteopontin, also called secreted phosphoprotein 1 (SPP1), and tenascin C (TNC), that promote lung metastasis. We demonstrate that both SPP1 and TNC are direct targets of the c‐Jun transcription factor. Exposure to multiple chemotherapies further exploits this JNK‐mediated axis to confer treatment resistance. Importantly, JNK inhibition or disruption of SPP1 or TNC expression sensitizes experimental mammary tumors and metastases to chemotherapy, thus providing insights to consider for future treatment strategies against metastatic breast cancer. Synopsis: JNK activity in breast cancer cells induces expression of the ECM and stem cell niche components osteopontin (SPP1) and tenascin C (TNC) to promote metastatic progression. This molecular axis is further induced upon exposure to chemotherapy and limits therapeutic efficacy. JNK activity in breast cancer cells is required for metastatic progression in vivo . JNK signaling drives a molecular network enriched in genes associated with wound healing and developmental processes, as well as mammary stem cell (MaSC) and ECM functions. Upon growth of metastatic nodules, the proportion of cancer cells with active JNK is reduced, but increases again in response to chemotherapy. Breast cancer cells can exploit chemotherapy‐induced JNK signaling to upregulate SPP1 and TNC and undermine the treatment. Abstract : JNK activity in breast cancer cells induces expression of the ECM and stem cell niche components osteopontin (SPP1) and tenascin C (TNC) to promote metastatic progression. This molecular axis is further induced upon exposure to chemotherapy and limits therapeutic efficacy.